Penurunan Hot Flashes pada Menopause dengan Senam Lansia: Reducing Hot Flashes in Menopause with Elderly Gymnastics - Juli Gladis Claudia; Nurnaningsih Ali Abdul; Nurhidayah Nurhidayah; Selvi Mohamad; Fatmawati Ibrahim; Eka Rati Astuti (Poltekkes Kemenkes Palu, 2022)
Introduction: One of the menopausal problems is hot flashes or chest burning with symptoms of night sweats, fatigue, insomnia, depression, anxiety, memory disorders, and urogenital symptoms, in some people experiencing different symptoms, and often causes impaired quality of life. If this condition cannot be overcome, it will develop into anxiety to stress which has a negative impact on women's social life which will stimulate the brain so that it can disrupt the hormonal balance and ultimately adversely affect the health of the body. Objective: The aim of the study was to analyze the effect of elderly exercise on reducing hot flashes in menopause. Methods: The type of research is Quasi Experiment with a one group pretest posttest design approach with the dependent variable is elderly exercise and the independent variable is hot flashes. Samples were all 66 menopausal people, analyzed using the Paired t test. Results: The results of the study after being tested, the mean pre-test value was 13.98 and the mean post-test was 21.00. The higher the mean value, there was a decrease in hot flashes before and after elderly exercise, meaning that there was a difference before and after treatment, the greater the mean value, the more means that the resulting test is evidenced by a p-value of 0.000 which is less than 0.05. Conclusion: it means that there is an effect of elderly exercise on reducing hot flashes in menopause. The conclusion is that there is a decrease in hot flushes in menopause before and after elderly exercise. ABSTRAK Pendahuluan: Salah satunya masalah menopause adalah hot flashes atau rasa panas didada dengan gejala berkeringat malam, fatigue, insomnia, depresi, ansietas, gangguan daya ingat, dan gejala urogenital, pada beberapa orang mengalami gejala berbeda, dan sering menyebabkan gangguan kualitas hidup. Jika kondisi ini tidak bisa diatasi akan berkembang menjadi cemas sampai dengan stres yang berdampak buruk pada kehidupan sosial perempuan yang akan merangsang otak sehingga dapat mengganggu keseimbangan hormon dan akhirnya berakibat buruk pada kesehatan tubuh. Tujuan: Tujuan penelitian untuk menganalisis pengaruh senam lansia terhadap penurunan hot flashes pada menopause. Metode: Jenis penelitian adalah Quasi Eksperiment dengan pendekatan one group pretest posttest design dengan variable terikat adalah senam lansia dan variable bebas adalah hot flashes. Sampel adalah semua menopause berjumlah 66 orang, dianalisis menggunakan uji Paired t test. Hasil: Hasil penelitian setelah diuji didapatkan nilai mean pre test 13,98 dan nilai mean post test 21,00 makin tinggi nilai mean maka ada penurunan hot flashes sebelum dan sesudah senam lansia, artinya ada perbedaan sebelum dan sesudah perlakuan makin besar nilai mean maka makin bermakna uji yang dihasilkan dibuktikan dengan nilai p-value 0,000 lebih kecil dari 0,05. Kesimpulan: artinya ada pengaruh senam lansia terhadap penurunan hot flashes pada menopause. Kesimpulan ada penurunan hot flushes pada menopause sebelum dan sesudah dilakukan senam lansia.